Effect of Statin Therapy on Cognitive Decline and Incident Dementia in Older Adults - Zhou, Zhen; Ryan, Joanne; Ernst, Michael E; Zoungas, Sophia; Tonkin, Andrew M; Woods, Robyn L; McNeil, John J; Reid, Christopher M; Curtis, Andrea J; Wolfe, Rory; Wrigglesworth, Jo; Shah, Raj C; et al. (Journal of the American College of Cardiology, 2021)
The neurocognitive effect of statins in older adults remain uncertain.BACKGROUNDThe neurocognitive effect of statins in older adults remain uncertain.The aim of this study was to investigate the associations of statin use with cognitive decline and incident dementia among older adults.OBJECTIVESThe aim of this study was to investigate the associations of statin use with cognitive decline and incident dementia among older adults.This analysis included 18,846 participants ≥65 years of age in a randomized trial of aspirin, who had no prior cardiovascular events, major physical disability, or dementia initially and were followed for 4.7 years. Outcome measures included incident dementia and its subclassifications (probable Alzheimer's disease, mixed presentations); mild cognitive impairment (MCI) and its subclassifications (MCI consistent with Alzheimer's disease, other MCI); and changes in domain-specific cognition, including global cognition, memory, language and executive function, psychomotor speed, and the composite of these domains. Associations of baseline statin use versus nonuse with dementia and MCI outcomes were examined using Cox proportional hazards models and with cognitive change using linear mixed-effects models, adjusting for potential confounders. The impact of statin lipophilicity on these associations was further examined, and effect modifiers were identified.METHODSThis analysis included 18,846 participants ≥65 years of age in a randomized trial of aspirin, who had no prior cardiovascular events, major physical disability, or dementia initially and were followed for 4.7 years. Outcome measures included incident dementia and its subclassifications (probable Alzheimer's disease, mixed presentations); mild cognitive impairment (MCI) and its subclassifications (MCI consistent with Alzheimer's disease, other MCI); and changes in domain-specific cognition, including global cognition, memory, language and executive function, psychomotor speed, and the composite of these domains. Associations of baseline statin use versus nonuse with dementia and MCI outcomes were examined using Cox proportional hazards models and with cognitive change using linear mixed-effects models, adjusting for potential confounders. The impact of statin lipophilicity on these associations was further examined, and effect modifiers were identified.Statin use versus nonuse was not associated with dementia, MCI, or their subclassifications or with changes in cognitive function scores over time (p > 0.05 for all). No differences were found in any outcomes between hydrophilic and lipophilic statin users. Baseline neurocognitive ability was an effect modifier for the associations of statins with dementia (p for interaction < 0.001) and memory change (p for interaction = 0.02).RESULTSStatin use versus nonuse was not associated with dementia, MCI, or their subclassifications or with changes in cognitive function scores over time (p > 0.05 for all). No differences were found in any outcomes between hydrophilic and lipophilic statin users. Baseline neurocognitive ability was an effect modifier for the associations of statins with dementia (p for interaction < 0.001) and memory change (p for interaction = 0.02).In adults ≥65 years of age, statin therapy was not associated with incident dementia, MCI, or declines in individual cognition domains. These findings await confirmation from ongoing randomized trials.CONCLUSIONSIn adults ≥65 years of age, statin therapy was not associated with incident dementia, MCI, or declines in individual cognition domains. These findings await confirmation from ongoing randomized trials.